P113 How has COVID-19 affected the treatment of osteoporosis? The answers from a global survey. (26th April 2021) - Fuggle, Nicholas R; Singer, Andrea; Harvey, Nicholas; Reginster, Jean-Yves; Cooper, Cyrus; Greenspan, Susan
Abstract: Background/Aims The COVID-19 pandemic has had profound effects on the health of the global population both directly, via the sequelae of the infection, and indirectly, including the relative neglect of chronic disease management. Together the International Osteoporosis Federation and National Osteoporosis Foundation sought to ascertain the impact on osteoporosis management. Methods Questionnaires were electronically circulated to a sample of members of both learned bodies and included information regarding the location and specialty of respondents, current extent of face to face consultations, alterations in osteoporosis risk assessment, telemedicine experience, alterations to medication ascertainment and delivery, and electronic health record (EHR) utilisation. Responses were collected, quantitative data analysed, and qualitative data assessed for recurring themes. Results Responses were received from 209 healthcare workers from 53 countries, including 28% from Europe, 24% from North America, 19% from the Asia Pacific region, 17% from the Middle East, and 12% from Latin America. Most respondents were physicians (85%) with physician assistants, physical therapists and nurses/nurse practitioners represented in the sample. The main three specialties represented included rheumatology (40%), endocrinology (22%) and orthopaedics (15%).In terms of the type of patient contact, 33% of respondents conducted telephone consultations and 21% video consultations. Bone mineral density assessment by dual-energy x-ray absorptiometry (DXA) usage was affected with only 29% able to obtain a scan as recommended. The majority of clinicians (60%) had systems in place to identify patients receiving subcutaneous or intravenous medication, and 43% of clinicians reported difficulty in arranging appropriate osteoporosis medications during the COVID-19 crisis. Conclusion To conclude through surveying a global sample of osteoporosis healthcare professionals, we have observed an increase in telemedicine consultations, delays in DXA scanning, interrupted supply of medications and reductions in intravenous medication delivery. Disclosure N.R. Fuggle: None. A. Singer: None. N. Harvey: None. J. Reginster: None. C. Cooper: None. S. Greenspan: None.